Adaptive fuzzy dual‐performance fault‐tolerant control for interconnected nonlinear systems. (30th May 2021) - Hao, Siwen; Xue, Hong; Pan, Yingnan
Summary: This article focuses on the decentralized adaptive fuzzy fixed‐time fault‐tolerant control issue for the error‐constrained interconnected nonlinear systems with unknown actuator faults possessing dead zone. The unknown nonlinear functions can be modeled via fuzzy logic systems. By utilizing the parameter estimation method, the effect of unknown actuator faults possessing dead zone can be compensated. To guarantee the predefined dynamic performance of state tracking errors, the barrier Lyapunov functions and prescribed performance functions are introduced. Then, a dual‐performance fault‐tolerant control method that can guarantee fast transient performance and predefined performance of state tracking errors is proposed via using the decentralized backstepping technique. In addition, on the basis of the Lyapunov stability theory and the fixed‐time criterion, it is proved that the predefined performance of full‐state errors and the stability of closed‐loop systems can be guaranteed. Finally, two numerical examples are provided to illustrate the effectiveness of the proposed control scheme.